Washington's secret war : the hidden history of Valley Forge - Fleming, Thomas J. (New York : Smithsonian Books/Collins, 2005)
Discusses Valley Forge within the larger context of the Revolutionary War, linking the winter stay of the Continental Army during 1777 and 1778 to such events as the negotiations with the French and the maneuvering of the Continental Congress.
General George Washington: loser -- Revels and redcoats -- Ideologues front and center -- Playing the insult card -- Enter the committee in camp -- "Congress does not trust me" -- Discipline from a baron -- From anxiety to exultation -- The follies of spring -- General double trouble -- A moment at Monmouth -- Epilogue: Two visits to Valley Forge.
Includes bibliographical references (p. [351]-375) and index.
Keywords: Valley Forge (Pa.) -- History, Military -- 18th century; Washington, George, -- 1732-1799 -- Military leadership; United States. -- Continental Army -- History; Washington, George, -- 1732-1799 -- Headquarters -- Pennsylvania -- Valley Forge; United States -- History -- Revolution, 1775-1783 -- Campaigns; United States -- Politics and government -- 1775-1783.